ChemInform Abstract: Heterometallic Sulfide Cluster [Ag6Sn6S20]10‐: Solvothermal Syntheses and Characterizations of Silver Thiostannates with Lanthanide Complex Counter Cations. Issue 32 (August 2015) - Han, Jingyu; Liu, Yun; Lu, Jialin; Tang, Chunying; Wang, Fang; Shen, Yali; Zhang, Yong; Jia, Dingxian
Abstract The new hybrid silver thiostannates (enH)4[Ln(en)4]2 [Ag6Sn6S20]·3en (Ln: Er, Tm, Yb) are solvothermally prepared from mixtures of Ln2O3, Ag, Sn, and S in en (180 °C, 6 d).